1999
DOI: 10.1038/sj.bjp.0702342
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of endothelin‐1 and magnesium sulphate on regional blood flows in conscious rats, by the coloured microsphere reference technique

Abstract: 1 There is evidence to suggest that magnesium (Mg 2+ ) is bene®cial in the treatment of a number of conditions, including pre-eclampsia and acute myocardial infarction. The mode of action of Mg 2+ in these conditions is not clear, although the vasodilator properties of Mg 2+ are well documented both in vitro and in vivo. 2 Previously, we demonstrated that i.v. infusion of magnesium sulphate (MgSO 4 ) alone, or in the presence of vasoconstrictors, caused increases in¯ow and conductance in the common carotid, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Magnesium has in vivo and in vitro vasodilator properties, and MgSO 4 injection has been reported to reduce total peripheral resistance and counteract the vasospasm induced by vasoconstrictor substances, such as endothelin-1, in several vascular beds. 32 This result could explain the preserved normal histological structure and the amelioration of hypertension in the PRE þ MgSO 4 group in the current study. Similarly, MgSO 4 was able to relieve coronary Table 3 Morphometric criteria of pups in the CON-P, preeclampsia (PRE) and PRE þ MgSO 4 groups of rats at day 21 of pregnancy vasospasms, increase blood flow and improve endothelial function, leading to a good response in several ischemic cardiac problems.…”
Section: Discussionsupporting
confidence: 52%
“…Magnesium has in vivo and in vitro vasodilator properties, and MgSO 4 injection has been reported to reduce total peripheral resistance and counteract the vasospasm induced by vasoconstrictor substances, such as endothelin-1, in several vascular beds. 32 This result could explain the preserved normal histological structure and the amelioration of hypertension in the PRE þ MgSO 4 group in the current study. Similarly, MgSO 4 was able to relieve coronary Table 3 Morphometric criteria of pups in the CON-P, preeclampsia (PRE) and PRE þ MgSO 4 groups of rats at day 21 of pregnancy vasospasms, increase blood flow and improve endothelial function, leading to a good response in several ischemic cardiac problems.…”
Section: Discussionsupporting
confidence: 52%
“…25) Mg 2+ also attenuates the effects on the cerebral arteries of endothelin-1 and oxyhemoglobin, which are considered to be important potent vasoconstrictors after SAH. 7,11) The present study demonstrated that intra-cisternal infusion of magnesium sulfate solution has a vasodilatory effect on the spastic cerebral arteries of patients with symptomatic vasospasm following aneurysmal SAH. The effect of magnesium infusion was most prominent in the arteries near to the cisternal drainage placement because the repeated angiography was performed shortly after the start of infusion (3 hours).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, Mg 2þ can inhibit flux through voltagedependent Ca 2þ channels in vascular smooth muscle cells, 3 and could thereby limit inappropriate vasoconstrictor responses in the wake of SD in injured tissues. Prior work has shown that intracisternal Mg 2þ reduces the frequency and the depolarization time of SD and it reduces lesion volume following subarachnoid hemorrhage in rats.…”
Section: Introductionmentioning
confidence: 99%